Attitudes of Teachers and Principals of Public Schools in Mafraq Governorate Towards E-learning - Alrishoud, Zainb Hassan Ahmad (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the Attitudes of Teachers and Principals of Public Schools in Mafraq Governorate Towards E-learning, and the study sample consisted of (325) directors and teachers from the Directorate of Education and Teaching in the Governorate of Mafraq, who were chosen in a simple random way, and the descriptive approach and the questionnaire were used as a tool for data collection. Attitudes of public school teachers in the governorate of Mafraq towards e-learning came in a moderate degree, with an average of (3.36) and a percentage (67.2%), while the attitudes of school principals towards e-learning were high, with an average of (3.79), and with a percentage (57.8%). It also found that there are statistically significant differences in the estimates of the study sample towards e-learning due to the variable of gender, the nature of work in favor of females and the nature of work for the benefit of teachers, and in light of the results of the study, a set of recommendations were presented, the most prominent of which is an increase in the use of distance learning and its inclusion within the courses Students to be able to fully benefit from them, and to give training courses to teachers, especially with modern strategies for dealing with electronic applications that work to attract students' attention.
Keywords: Attitudes; School teachers; School principals; E-learning